Computational Processing of the Portuguese Language: 8th International Conference, PROPOR 2008 Aveiro, Portugal, September 8-10, 2008 : Proceedings - Carbonell, Jaime G; Siekmann, Jörg; Teixeira, António; Quaresma, Paulo (Lecture Notes in Computer Science, 2008)
This book constitutes the thoroughly refereed proceedings of the 8th International Workshop on Computational Processing of the Portuguese Language, PROPOR 2008, held in Aveiro, Portugal, in September 2008. The 21 revised full papers and 16 revised short papers presented were carefully reviewed and selected from 63 submissions. The papers are organized in topical sections on speech analysis; ontologies, semantics and anaphora resolution; speech synthesis; machine learning applied to natural language processing; speech recognition and applications; natural language processing tools and applications; posters.